Coping Ability and Promotion Countermeasures of Medical and Health Institutions Reputation Crisis: A Case Study in Hubei Province - Yang Liu; Yang Liu; Xiaofang Li; Xiaofang Li; Rui Ding; Tianrun He; Xian-jia Wang (Frontiers Media S.A., 2022)
At present, the doctor-patient relationships in Chinese medical and health institutions (MHI) are increasingly tense, and the reputation crisis challenges are being faced by MHI more frequently. However, the reputation crisis management level of the MHI is directly related to the future development and construction of the MHI and is an important management link that cannot be ignored. Therefore, how to quantify the impact of the relevant crisis on hospitals has become a major problem. First of all, this paper uses the situational crisis communication theory (SCCT) to combine the characteristics of hospital reputation crisis with the theory and classification of MHI reputation crisis from three perspectives: victim crisis, accidental crisis, and preventable crisis. Second, a more comprehensive analysis of MHI reputation crisis management model is conducted in the research cases, based on the relevant data of Union Hospital, Tongji Medical College Huazhong University of Science and Technology (UH), Tongji Hospital, Tongji Medical College Huazhong University of Science and Technology (TJ), Zhongnan Hospital of Wuhan University (ZN), Renmin Hospital of Wuhan University (RM), and Maternal and Child Hospital of Hubei Province (MC). Third, we divide MHI reputation positioning into four types, namely robust, growth, fragile, and sensitive, and innovate SCCT to build a new MHI crisis classification type. Finally, this paper provides appropriate crisis management strategies for sample MHI based on the above examples and theories. Furthermore, we realize the lifecycle management of MHI reputation by identifying, evaluating and responding to reputation issues. This study provides a theoretical reference for the MHI reputation crisis management level and the adjustment of future management strategies.